Gold prospecting in tropical regions using satellite remote sensing data: case study from Malaysia goldfields - Pour, Amin Beiranvand (2015)
This study presents a remote sensing approach for geological mapping aimed at the detection of hydro-thermal alteration minerals and structural features for initial stages of gold exploration in tropical environments. Recent challenge is to utilize the most suitable recent generation of remote sensing data and innovative image processing approaches for detecting hydrothermal alteration zones and structural features associated with epithermal and polymetallic vein-type mineralization in tropical environments. In this investigation, two gold mining districts in Malaysia were selected as case studies , namely the Bau gold mining district in the State of Sarawak, East Malaysia, on the island of Borneo and Penjom goldfield in the state of Pahang, Peninsular Malaysia . The climate of both study regions is tropical with persistent cloud coverage and very dense vegetation cover. Gold mineralization in these areas is structurally controlled and associated with hydrotherm al mineral assemblages. Various types of remote sensing data were tested for hydrothermal alteration mapping and structural analysis associated with gold mineralization in the study areas. The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), Landsat Enhanced Thematic Mapper+ (ETM+), Hyperion and Phased Array type L-band Synthetic Aperture Radar (PALSAR) data sets were used in this study. Processing of the image data was performed using some developed methods that could reduce or remove the spectral effects of vegetation to detect alteration mineral zones and geological structures associated with gold mineralization in the study areas. Vegetation, mineral and lithological spectral indices have been applied to ASTER bands. Directed principal components (DPC) analysis was implemented to four special band ratio images of ETM+, including 3/1,4/3, 5/7 and 5/4. Linear spectral unmixing (LSU) was applied to visible and near-infrared radiation (VNIR) and shortwave infrared (SWIR) bands of Hyperion. Directional filters were applied to PALSAR data. Results of the DPC analysis of four appropriate ETM+ band ratios produced DPe images, allowing the removal of spectral effects of vegetation from ETM+ data and the detection of iron-oxide-rich rocks or gossan and clay-rich zones. Results derived from VNIR and SWIR bands of Hyperion represented iron oxidel hydroxide and clay-rich zones using LSU technique. Numerous tectonic lineaments with consistent variations in trend, length and density associated with different lithological units outcropping in the study areas were detected using PALSAR data. Geological tectonic structures such as faults , fractures and anticline were detected in the PALSAR resultant image derived from directional filters (NS, NE-SW, and NW-SE). Structural features associated with fault-related rocks and hydrothermal alteration zones were identified as highly potential areas for prospecting gold mineralization. Of particular importance to exploration are the intersection of ENE and NNE structure element in the Bau area and N-S, NE-SW, NNWSSE and ESE-WNW mineralized trends in the Penjom region, respectively. Results of this study demonstrate the applicability of integrated satellite remote sensing data to assist more feasible gold exploration plans in the study regions and reduction of exploration costs for epithermal or polymetallic vein-type mineralization in tropical environments.